2010
DOI: 10.1021/bi100780t
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis, Overexpression, and Kinetic Characterization of Pyruvate Kinase from Methicillin-ResistantStaphylococcus aureus

Abstract: Novel antimicrobial targets are urgently needed to overcome rising antibiotic resistance of important human pathogens including methicillin-resistant Staphylococcus aureus (MRSA). Here we report the essentiality and kinetic properties of MRSA pyruvate kinase (PK). Targetron-mediated gene disruption demonstrated PK is essential for S. aureus growth and survival, suggesting that this protein may be a potential drug target. The presence of the pfk (6-phosphofructokinase)-pyk operon in MRSA252, and the nonessentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 62 publications
(109 reference statements)
2
52
0
Order By: Relevance
“…As a result of this analysis, pyruvate kinase (PK), the product of a single-copy gene, was identified as a highly connected hub protein in MRSA. Furthermore, we also found that PK is absolutely essential for S. aureus viability based upon PK antisense and gene disruption experiments (44). The essential requirement for PK for bacterial growth was also reflected by its high enzymatic activity during the exponential phase of the S. aureus life cycle.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…As a result of this analysis, pyruvate kinase (PK), the product of a single-copy gene, was identified as a highly connected hub protein in MRSA. Furthermore, we also found that PK is absolutely essential for S. aureus viability based upon PK antisense and gene disruption experiments (44). The essential requirement for PK for bacterial growth was also reflected by its high enzymatic activity during the exponential phase of the S. aureus life cycle.…”
mentioning
confidence: 62%
“…The essential requirement for PK for bacterial growth was also reflected by its high enzymatic activity during the exponential phase of the S. aureus life cycle. Taken together, these findings provide a clear rationale for selecting PK as a novel, candidate drug target (44).…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Thus, identification of new targets for antibacterial development based upon novel scaffolds with unique mechanisms of action are critically needed (3). To this end, we recently identified pyruvate kinase (PK), an evolutionarily conserved, highly connected essential hub protein in MRSA, with structural features distinct from the mammalian orthologs, as a novel candidate drug target (1,4,5). Using structural modeling, virtual data base screening, and enzyme activity assays in combination with medicinal chemistry, we recently identified low micromolar selective inhibitors of MRSA PK exhibiting strong antibacterial activity against Staphylococci and a range of other Gram-positive bacteria such as Enterococcal and Streptococcal species with low micromolar minimal inhibitory concentration (MIC) values (5).…”
mentioning
confidence: 99%
“…Sequence alignment between MRSA and human PKs revealed particular sequence divergence in domain C (e.g. sites for effector binding), which is involved in formation of the small interfaces between the C domains of adjacent PK subunits providing tetramer rigidity and efficient catalytic activity of the enzyme (2,4).…”
mentioning
confidence: 99%